Removal of the direct navy-blue dye on modified coffee bean (2020)
The presence of dyes in water bodies inhibits the penetration of light, affecting the flora and fauna of these ecosystems, which is why, greater efforts are made to eliminate them before being poured. This study allowed the removal of the direct navy-blue dye (DNB), using activated carbon prepared from coffee beans and H3PO4. The experimental methodology began with the preparation of three types of activated carbon by varying the concentration of H3PO4 (20, 40 and 60% m/v). Texture properties were evaluated by adsorption-desorption isotherms with N2 to 77 K, the identification and quantification of organic functional groups, mainly acids, with FTIR and the Boehm method, respectively. Batch adsorption experiments were performed by varying the initial dye concentration (5, 10, 50, 75, 100 and 200 mg/dm3) to 25 °C and, the adsorption kinetics was determined. Both coffee beans and activated carbons have an acidic nature with surface area development between 519 and 771 m2/g. With respect to the batch study, a monolayer and multilayer growth was observed on a heterogeneous surface. Activated carbon prepared with 20% of H3PO4 recorded the highest removal capacity with a value of 25.8 mg/g. The kinetic model of pseudo second order was the one that best fit to the experimental data (R2 > 0.98). It can be concluded that the coffee bean treated with H3PO4 is an efficient adsorbent to remove DNB from aqueous solutions.